The Interplay of Human Resource Practices and Employee Innovative Behavior in Employee Performance - Ami Fitri Utami; Catra Aryasatya (Australasian Accounting, Business and Finance Journal, 2023)
The COVID-19 pandemic greatly affected the global economy with lockdown measures and reduced economic activity. This study investigates the relationship between employee innovative behavior, HR practices implementation, and performance at one of the biggest car distributors in Indonesia. The study determines the impact of employee's innovative ideas in daily work activities and changes in HR practices on the company's recent performance improvements. The research uses a quantitative approach by using a questionnaire of 120 employee respondents and applying the PLS-SEM (Partial Least Square – Structural Equation Modeling) to analyze the data. The result shows that employee's innovative behavior and HR practices significantly influence employee performance.
Keywords: Automotive Company; COVID-19; Employee Innovative Behavior; Human Resource Practices